Optimization of Lithium Separation from NCA Leachate Solution: Investigating the Impact of Feed Concentration, Pressure, and Complexing Agent Concentration - Mustika, Pra Cipta Buana Wahyu; Suryanaga, Edward Chandra; Perdana, Indra; Sutijan, Sutijan; Astuti, Widi; Petrus, Himawan Tri Bayu Murti; Prasetya, Agus (ASEAN Journal of Chemical Engineering, 2023)
Recycling lithium batteries (LIB) has emerged as an attractive solution in the global pursuit of environmentally friendly practices. The aim of achieving zero–waste hydrometallurgical technology is within reach. This research focuses on utilizing the low-pressure nanofiltration process to address this challenge by separating lithium ions from other ions and achieving a desirable permeate flux. The NCA battery leachate concentrate was obtained through a hydrometallurgical process involving sulfuric acid–peroxide. To ensure the prevention of potential nanofiltration membrane (TS80) fouling, the concentrate is initially filtered using an ultrafiltration membrane (UH004) to remove any particles. The research investigates the impact of pressure (4, 6, and 7 bar), solution concentration (concentrate, 10x, and 50x dilution), and the concentration of the complexing agent (EDTA) on the desired separation performance. The investigation reveals that pressure variations exhibit consistent rejection rates, remaining stable above 80%. A similar trend is observed with the addition of EDTA, which consistently yields rejection rates above 80%. However, when examining different feed concentrations, the rejection of lithium falls below 80% for leachate concentrates. In summary, satisfactory results are obtained by employing nanofiltration with a TS80 membrane at a pressure of 7 bar, a dilution factor of 10x, and using a 0.02M EDTA complexing agent. Meanwhile, it was found that the separation factors (Li⁺/Ni²⁺ = ~8.6, Li⁺/ Co²⁺ = ~7.3, Li⁺/Al³⁺ = ~4.9) and permeate flux ±46.58 L m⁻² h⁻¹. The findings demonstrate good selectivity along with relatively high flux.